The measurement of damage initiation, particle adhesion and cohesive strength from traction displacement curves of a nano-toughened epoxy. (October 2016) - Mc Auliffe, D.; Karac, A.; Murphy, N.; Ivankovic, A.
Abstract: In this work the deformation behaviour of a nano-toughened epoxy adhesive is measured at different levels of stress triaxiality. The test method consists of a notched axisymmetric adhesive layer loaded in tension. The recorded traction displacement curves were analysed numerically and it was found that the measured peak stress corresponds to the intrinsic cohesive strength, σ max of the material. This method allows experimental measurement of σ max for use in cohesive zone models of fracture. Additional features of the traction displacement curves include a kink that corresponds to particle debonding at a critical hydrostatic stress. By application of the Mori–Tanaka model, the relationship between the experimental measurements and particle/matrix adhesion is described.